Synthesis of some new fluorine substituted thiobarbituric acid derivatives as anti HIV1 and cyclin-dependent kinase 2 (CDK2) for cell tumor division: Part I - Al-Harbi, Abdulrahman Salim; Abdel-Rahman, Reda Mohammady; Asiri, Abdullah Mohamed (European Journal of Chemistry, 2015)
New potential enzyme inhibitors, fluorine-substituted thiobarbituric acid derivatives (2, 3, 9, 8 and 12) and their fused/isolated heterocyclic nitrogen systems (5, 6, 10 and 14) have been obtained from heterocyclization of fluorinated N, Nʹ-disubstituted thiourea (1, 7 and 11) with malonic acid followed by ring closure reactions with primary nitrogen reagents. Structures of the synthesized products have been deduced from their elemental analysis and spectral data. Anti-HIV-1 and inhibition of cyclin-dependent kinase2 (CDK2) for cell tumor division for the synthesized compounds were also evaluated.